(3GNJdGa GdbQGA GdSHYI aj GdHGAGJ hGdJGAGJ hGdKGAGJ hGdfhfGJs - (3YHO GdefYe Hf YHjO Gddg Hf ZdHhf Hf GdeHGQc, CHh GdWqjH, J (B389 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj SHH GdCSHGH hGSJYHO GdCQHGH hgRe GdCMRGH hedc GdQbGH s
(3BNQgG (B:s
(3hfSCdg Cf jLYd Pdc dhLgg aEfg cQje LhGO eJaVd Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs